Using GNSS signals as a proxy for SAR signals: Correcting ionospheric defocusing. Issue 2 (3rd February 2016) - Mannix, Christopher R.; Belcher, David P.; Cannon, Paul S.; Angling, Matthew J.
Abstract: Ultrahigh frequency space‐based synthetic aperture radar (SAR) can suffer from the degrading effects of a scintillating ionosphere which modulates both the phase and the amplitude of the radar signal. In this paper, we use Global Navigation Satellite System (GNSS) signals to synthesize an L‐band SAR point spread function (PSF). The process of transforming the GNSS signal to the equivalent SAR PSF is described. The synthesized PSF is used to explore the possibility of using a phase correction determined from a point target in a SAR image to correct the ionospheric degradation. GNSS data recorded on equatorial Ascension Island during scintillation events are used to test the feasibility of this approach by applying a phase correction to one GNSS receiver from another located along a magnetic east‐west baseline. The peak‐to‐sidelobe ratios of the synthesized L‐band SAR point spread functions before and after the correction are compared, and it is shown that this approach improves the L‐band PSF over distances of 3000 m in the ionosphere, corresponding to 6000 m on the ground. Key Points: GNSS carrier amplitude and phase can be used to synthesize the SAR point spread function Two position GNSS measurements can be used to test mitigation of ionospheric effects on SAR Corrections can be made over a distance of 3 km in the ionosphere ( 6 km on the ground)